Pengembangan Website Edukatif BUDIMAN (Budaya Islam Generasi Beriman) untuk Membiasakan Kalimah Tayyibah bagi Siswa Kelas 3 SD - Ani Nur Aeni; Yudi Guntoro; Farraj Azman Muyasar; Liza Ananda Putri (YASIN, 2026)
Although the use of digital learning media has received considerable attention in previous studies, research that specifically discusses the development of website-based learning media integrating various interactive features in Islamic Education learning, particularly on the topic of kalimah ṭayyibah in elementary schools, remains limited. This study aims to develop and evaluate the feasibility of the BUDIMAN educational website (Budaya Islami untuk Generasi Beriman) as an interactive learning medium for third-grade elementary school students. This study used a qualitative approach with the Design and Development (D&D) method through the ADDIE model, involving 37 students selected through purposive sampling. Data were collected through observation, interviews, questionnaires, and documentation, and then analyzed using descriptive qualitative analysis. The results showed that the BUDIMAN website was in the very feasible category based on expert validation, with a material expert validation percentage of 100% and a media expert validation percentage of 97.5%. In addition, students showed high enthusiasm and engagement during the learning process. These findings contribute to the development of interactive digital learning media and broaden understanding of technology integration in Islamic Education learning in elementary schools. This study concludes that interactive website-based learning media have an important role in increasing students’ engagement and understanding of kalimah ṭayyibah material, so the use of innovative digital media needs to be optimized to support more effective learning.